A Combined DPSIR Framework and Logical Framework Approach for Sustainable Water Resources Management in the Lagoon Floodplain: 10.32526/ennrj/21/202200170 - Teerakul, Benchawan; Rongsayamanont, Chaiwat; Darnsawasdi, Rotchanatch; Kosolsaksakul, Peerapat (Environment and Natural Resources Journal, 2023)
This article describes a combination of the driver-pressure-state-impact-response (DPSIR) framework and the logical framework approach (LFA) to develop water management strategies for a lagoon floodplain in Thailand. The DPSIR framework identified the cause-effect relationship between water and anthropogenic activities. LFA developed management strategies based on a systematic and logical approach. DPSIR analysis for the issue of water shortages for irrigated areas revealed the need for income from agriculture is a major driver, as indicated by agricultural development policy. The driver exerted pressure on increasing irrigation water demand, which increased the risk of a water shortage. The impact of water shortage was indicated by loss of farmer income. Existing responses led to inadequate problem-solving, for example, the promotion of mixed farming. Using data captured from DPSIR analysis for LFA analysis, proposed strategies to address the root causes of “ineffective irrigation water allocation” focused on improving (1) the performance of rotating irrigation systems; (2) monitoring water allocation; and (3) water use efficiency. The strategies developed using the combined DPSIR framework and LFA are effective because: (1) this method provides insight into complex water systems; (2) the strategies are developed logically to solve the problem at its root cause; and (3) there is intensive stakeholder participation and in-depth study of the area. This method is a helpful tool for developing a management strategy for a complex water system and is suitable for application by decision-makers. Stakeholder verification is required for future research to ensure that the strategies are appropriate and capable of being implemented.